Impact Of Gamma-Irradiation On The Morphology And Mitosis In Cluster Bean [Cyamopsis Tetragonoloba (L.) Taub.] (Applied Biological Research, 2020)
Induced mutagenesis is an important tool for crop improvement and gamma  (γ) ray is one of the effective physical ionizing mutagens. The present pilot  study was aimed to assess the effect of γ-irradiation on mitotic cells in cluster  bean (Cyamopsis tetragonoloba (L.) Taub.). The seeds of cluster bean were  treated with different doses of γ rays viz., 0, 100, 200, 300, 400 and 500 Gy to  analyze the effect of γ-rays on meristematic root tips. Active mitotic index  and total abnormality percentage were assessed. Increasing dose of γ rays  negatively influenced AMI. Higher doses severely reduced germination and  seedling height, although the initial dose of 100 Gy γ-irradiation significantly  enhanced them as compared to the control. The irradiated seeds showed  numerous chromosomal variations such as scattering, c-metaphase, bridge  formation, etc. The evidences revealed that γ-rays have mutagenic effect at  mitotic level and induced decline in mitotic activity and influenced the entity  of chromosomal morphology. The study also revealed that lower doses of γ irradiation can be effective in agricultural endeavours.
Keywords: Active mitotic index; Cyamopsis tetragonoloba; gamma rays; mutagen; TAB